PENGARUH PEMBERIAN KOMPOS GULMA SIAM TERHADAP INTENSITAS SERANGAN ORGANISME PENGGANGGU TANAMAN CABAI - Eko Apriliyanto; Rr. Mustika Pramudya A. (Jurnal Ilmiah Media Agrosains, 2014)
The purpose of the study is to determine the effect of siam weed compost toward the attact intensity of plant pest organism and the effect toward red chili products. The research was conducted in experimental garden of Politechnic Banjarnegara using a Randomized Block Design. The treatment used five types of fertilizers. They were control/ without fertilizer, NPK (urea 400 kg/ha, SP36 200 kg/ha, and KCl 200 kg/ha), chicken manure 40 ton/ha, goat manure 40 ton/ha, cow dung manure 40 ton/ha, and siam weed compost 40 ton/ha. Each treatment was repeated 4 times, so there were 24 experimental units. The result showed major pest that attact chili plant were green leafhopper (Empoasca sp.) and aphids (Aphid sp.) The attact intensity of green leafhopper pest by providing siam weed compost and other fertilizers did not show significantly different, but the chili plant did not show any green leafhopper attact. The attact intensity of aphids by providing siam weed compost and other fertilizers were also not significanly different from the mean intensity of the attact on the siam weed compost treatment wich required 19,08%. The entire treatment can not improve the result both of the chili fresh weigh and the chili dry weight wich are 79,31 g and 14,67 g each in siam weed compost treatment. Plant fresh weigh is 59,95 g at siam weed compost from treatment did not show significantly different from either control plant and the other fertilizer treatment giving siam weed compost, goat manure, and chicken manure can increase plant dry weight wich are 17,59 g, 18,55 g, and 18,55 g.